Long-term observations of polar mesosphere summer echoes using the ESRAD MST radar - Smirnova, Maria (Luleå tekniska universitet, Rymdteknik, 2011)
Polar Mesosphere Summer Echoes (PMSE) are strong radar echoes observed from altitudes of 80-90 km in polar regions, during summer time. PMSE are closely related to the fascinating atmospheric phenomenon known as noctilucent clouds (NLC). Since it has been suspected that NLC could respond to climate change in the mesosphere, they have attracted considerable interest in the scientific community during recent years. However, continuous visual or photographic NLC observations suffer from weather restrictions and the human factor. In contrast, PMSE radar measurements can easily be made over a long interval and are very attractive for long-term studies of the atmospheric parameters at the polar mesopause. This thesis uses the world’s longest data set of PMSE observations made by the same radar at the same place. Since 1997 these measurements have been carried out with the 52 MHz ESRAD MST radar located near Kiruna in Northern Sweden. The data set for 1997-2008 has been used for studies of diurnal, day-to-day and year-to-year variations of PMSE. We showed that PMSE occurrence rate and volume reflectivity on a daily scale show predominantly semidiurnal variations with the shape of the diurnal curves remaining consistent from year to year. We found that day-to-day and inter-annual variations of PMSE correlate with geomagnetic activity while they do not correlate with mesopause temperature or solar activity. We did not find any statistically significant trends in PMSE occurrence rate and length of PMSE season over 1997-2008. The thesis also presents also a new, independent calibration method, which can be used to estimate changes in transmitter output and antenna feed losses from year to year (for example due to changes of antenna configuration) and allows making accurate calculations of PMSE strength. This method is based on radar-radiosonde comparisons in the upper troposphere/lower stratosphere region simultaneously with PMSE observations. Using this calibration we calculated the distribution of PMSE strength over ...